Gestão para resultados como política pública: uma análise da formação da agenda e alternativas em municípios brasileiros - Perdicaris, Priscilla Reinisch (2009)
Performance Management (PM) is being adopted as a central policy in some local governments throughout Brazil, as recently observed in some Brazilian states, as well as in the Federal Government, especially during Fernando Henrique Cardoso’s administration in mid-1990s. This dissertation explores the PM adoption process in three of the main municipalities of the South region – Curitiba, Porto Alegre and Joinville – using Kingdon’s (2003) multiple streams framework for agenda setting analysis, with the premise that management can be studied as a policy field. The principal idea is to identify the main actors and policy entrepreneurs, how they influence the problem definition, the generation of proposals and the political stream in those cases. In addition, it explores the context in which those streams were joined, creating “windows of opportunity” for the introduction of PM concepts in those municipalities.